Medicine, religion, and the body - Coleman, Elizabeth Burns, 1961-; White, Kevin, PhD. (International Studies in Religion and Society, 2010)
This book explores the ways in which the body is sacred in Western medicine, as well as how this idea is played out in questions of life and death, of the autopsy and of the meanings attributed to illnesses and disease. Ritual and religious modifications to, and limitations on what may be done to the body raise cross cultural issues of great complexity - philosophically and theologically, as well as sociologically - within medicine and for health care practitioners, but also, as a matter of primary concern for the patient. The book explores the ways in which medicine organises the moral and the immoral, the sacred and the profane; how it mediates cultural concepts of the sacred - of the body, of blood and of life and death.